Microfacies analysis and Depositional Basin Model of the Upper Cretaceous, Kurdistan Region, Northern Iraq - Gardy, Zahid M.; Ahmed, Sirwan H.; Baziany, Mushir M. (Sulaimani Journal for Pure and Applied Sciences, 2023)
This study focuses on the Upper Cretaceous system in the Zagros fold and thrust belt in the Kurdistan Region / Iraq. The impression of this study is created by the variety of formations, facies change, and age of the Cretaceous formations, as well as the different consequences of the contact situation between the formations, particularly the Qamchuqa-Bekhme and Kometan-Shiranish contacts formations. Through investigation, evaluation, and combination of results from Lithostratigraphy and Microfacies of seven sections in various locations of KRI/ Iraq, new paleogeography of the Late Cretaceous of Northern Iraq is constrained. The microfacies of entire Late Cretaceous formations in different sections outcome 16 sub-microfacies types demonstrating open marine deep shelf environment of Shiranish Formation, the entire reef (back-reef, fore-reef, reef body) environment of Bekhme Formation and pelagic open marine ramp depositional environment of Kometan Formation. The output results of stratigraphy and microfacies of Late Cretaceous depositional successions in the Kurdistan Region are paleogeography maps reconstruction. During the Turonian to Early Santonian periods, the Kurdistan Region and northern Iraq were presubduction basins due to the presence of open marine outer ramp carbonate of the Kometan Formation in the east (Sulaimaniyah province exceeding Hizop area) and inner shelf of Tanuma and Khasib formations in the center and west (Erbil province). Major regression and unconformities covered the West of the study region during the MiddleLate Santonian; the result of this regression degraded the entire inner shelf facies that deposited during Turonian-Early Santonian periods. During the Early-Middle Campanian, a foreland basin emerged in the extreme northeastern and the Kurdistan Region, which was covered by open marine of the Shiranish Formation and reef platform of the Bekhme Formation. The Kurdistan Region was an active foreland basin margin in the Upper Campanian-Maastrichtian, with a greatly expanded Tanjero Formation, an Aqra reef in the north, and an open marine Shiranish Formation in the center and west.
Keywords: Late Cretaceous; Conformities; Kometan Formation; Shiranish Formation; Bekhme Formation; Iraq